Gay Voice: stable marker of sexual orientation or flexible communication device? - Daniele, M. (2020)
Listeners rely on vocal features when guessing others’ sexual orientation. What is less clear is whether speakers modulate their voice to emphasize or to conceal their sexual orientation. We hypothesized that gay individuals adapt their voices to the social context, either emphasizing or disguising their sexual orientation. In Study 1 (n = 20 speakers, n = 383 Italian listeners and n = 373 British listeners), using a simulated conversation paradigm, we found that gay speakers modulated their voices depending on the interlocutor, sounding more gay when speaking to a person with whom they have had an easy (vs. difficult or no) coming out. Although straight speakers were always clearly perceived as heterosexual, their voice perception also varied depending on the interlocutor. Study 2 (n = 14 speakers and n = 309 listeners), comparing the voices of young YouTubers before and after their public coming out, showed a voice modulation as a function of coming out. The voices of gay YouTubers sounded more gay after coming out, whereas those of age-matched straight control male speakers sounded increasingly heterosexual over time. Combining experimental and archival methods, this research suggests that gay speakers modulate their voices flexibly depending on their relation with the interlocutor and as a consequence of their public coming out.